ACTIVITY OF DAILY LIVING (ADL) UNTUK MENINGKATKAN KEMAMPUAN RAWAT DIRI PADA PASIEN SKIZOFRENIA TIPE PARANOID - Afinia Sandhya Rini (LP2M IAIN Tulungagung, 2016)
JSA is a man (42 years) with mental disorder called schizophrenia disorganize type. The study aims to improve behavior independent in care of mom.Technique data collection is observation, interview and GRAFIS test. Intervention done 6 session with the approach behavior therapy the Activityof the Daily Living (ADL). Each session aims to teach on the subjects of behavior independent in care of mom and maintain clean liness in daily life. After conducted intervention, subject had more pattern of behavior independentin care of mom.Kata Kunci: Kemampuan Rawat Diri, Skizofrenia, Paranoid